2020
DOI: 10.31235/osf.io/5zc62
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consumers’ willingness to pay for plants protected by beneficial insects—Evidence from two stated-choice experiments with different subject pools

Abstract: 1Consumers' willingness to pay Consumers' willingness to pay for plants protected by beneficial insects-Evidence from two stated-choice experiments with different subject pools AbstractWe investigate consumers' willingness to pay for plants protected by beneficial insects and those protected by pesticides, respectively, as well as the influence of message framing on willingness to pay. We use basil, heather, and orchids as experimental objects and find evidence from two experiments that consumers prefer plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Our result that the use of beneficial insects, is the most preferred plant protection practice (Figure 3), is in line with results of Lehberger and Gr€ uner (2020) and Grygorczyk et al (2014), who report a preference among the general public in Germany and Canada for biological control over traditional pesticides.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our result that the use of beneficial insects, is the most preferred plant protection practice (Figure 3), is in line with results of Lehberger and Gr€ uner (2020) and Grygorczyk et al (2014), who report a preference among the general public in Germany and Canada for biological control over traditional pesticides.…”
Section: Discussionsupporting
confidence: 91%
“…Surveys from the EU conclude that organic food is preferable to nonorganic food (Meyerding et al, 2019), and the production of organic food without synthetic pesticides is a main motivator of consumption (Aertsens et al, 2011). Regarding the use of beneficial insects, Lehberger and Gr€ uner (2020) find evidence that German consumers prefer edible and inedible plants that beneficial insects protected, over those protected by pesticides. This agrees with findings from the USA, where Wollaeger et al (2015) found that consumers prefer floricultural crops labeled with "use of beneficial insects" over those labeled with "traditional insect control."…”
Section: Plant Protection Practicesmentioning
confidence: 97%